Effect of Positive Airway Pressure on Cardiovascular Outcomes in Coronary Artery Disease Patients with Nonsleepy Obstructive Sleep Apnea The RICCADSA Randomized Controlled Trial - (:unkn) unknown (AMER THORACIC SOC, 2016)
Rationale: Obstructive sleep apnea (OSA) is common in patients with coronary artery disease (CAD), many of whom do not report daytime sleepiness. First-line treatment for symptomatic OSA is continuous positive airway pressure (CPAP), but its value in patients without daytime sleepiness is uncertain. Objectives: To determine the effects of CPAP on long-term adverse cardiovascular outcome risk in patients with CAD with nonsleepy OSA. Methods: This single-center, prospective, randomized, controlled, open label, blinded evaluation trial was conducted between December 2005 and November 2010. Consecutive patients with newly revascularized CAD and OSA (apnea-hypopnea index >= 15/h) without daytime sleepiness (Epworth Sleepiness Scale score <10) were randomized to auto-titrating CPAP (n = 122) or no positive airway pressure (n = 122). Measurements and Main Results: The primary endpoint was the first event of repeat revascularization, myocardial infarction, stroke, or cardiovascular mortality. Median follow-up was 57 months. The incidence of the primary endpoint did not differ significantly in patients who did versus did not receive CPAP (18.1% vs. 22.1%; hazard ratio, 0.80; 95% confidence interval, 0.46-1.41; P = 0.449). Adjusted on-treatment analysis showed a significant cardiovascular risk reduction in those who used CPAP for >= 4 versus <4 hours per night or did not receive treatment (hazard ratio, 0.29; 95% confidence interval, 0.10-0.86; P= 0.026). Conclusions: Routine prescription of CPAP to patients with CAD with nonsleepy OSA did not significantly reduce long-term adverse cardiovascular outcomes in the intention-to-treat population. There was a significant reduction after adjustment for baseline comorbidities and compliance with the treatment.
Keywords: obstructive sleep apnea; coronary artery disease; cardiovascular outcomes; BLOOD-PRESSURE; FOLLOW-UP; THERAPY; CPAP; INTERVENTION; RATIONALE; ADHERENCE; HYPERTENSION; PREDICTORS; SURGERY